The affective mind: essays on Nietzsche's philosophical psychology - Fowles, CC (2020)
This thesis comprises three stand-alone papers, each concerning the philosophical psychology that can be drawn from the writings of Friedrich Nietzsche. The thread running throughout the thesis is a focus on affective states.